Faktor-Faktor yang Berhubungan dengan Kelelahan Kerja pada Industri Rumahan Pembuatan Kail Pancing UD. XYZ - Wicaksono, Febriawan Timur; Widjasena, Baju; Wahyuni, Ida (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
Work fatigue is a common problem in both formal and informal workplaces. Based on a preliminary study at UD XYZ, it is known that there is a decrease in productivity and the emergence of various complaints among fishing hook workers. Objective: To analyze several factors causing work fatigue in home industry workers making UD fishing hooks. XYZ. Methods: The study was conducted with cross-sectional study design at UD. XYZ, Bendar, Juwana, in June 2022 to 30 fishing hook making workers who were selected using the total sampling method. Data were collected using NBM and PSQI questionnaires, Respondent Data Sheets, and the RT Application. The results were analyzed using the chi-square test and Pearson's test. Statistical analysis using chi-square test and Pearson's test. Results: Based on the results of the chi-square test, the factors that affect work fatigue in workers are length of service (p = 0.010), sleep quality (p = 0.011), and the results of the Pearson test on work posture show a relationship (p = 0.017), while age (p=0.068) was not associated with work fatigue. Conclusion: Age has no relationship with work fatigue, while working period, sleep quality, and work posture have a relationship with work fatigue. Suggestions: Adjust the burden of the work according to the age of the worker, applying the rotation of job task, avoiding alcohol or caffeine consumption, and adjust the seat to the work desk.